(untitled) (Journal of Science and Technology, 2016)
Cape Coast Metropolis, which is close to Kakum forest, has its native forests being reduced to fragments. Biodiversity in these forest reserves are exposed to the threat of being cleared over night as a result of urbanization. There are reported cases of some rare or potential medicinal plant species that have disappeared from the Cape Coast environ and is worth noting that basic knowledge of the organisms that make up most of the ecosystems in these remnant forests are woefully inadequate. In this study, inventory of vertebrates and invertebrates were undertaken in five remnant forests in Cape Coast. The study sites were surveyed for small terrestrial mammals, large mammals, avifauna, herpetofauna and invertebrates. From the inventory taken, 15604 species of invertebrates belonging to 51 families, 83 species of birds belonging to 30 families were sampled. Furthermore 14 species of mammals belonging to 8 families and 8 species of her- petofauna were also sampled. Although these species were of least concern under IUCN cate- gory, it is important to protect these native forests from total destruction. Benefits such as the protection of numerous native pollinators and biological control agents can be derived when these reserves are protected. Furthermore, such reserves can be developed to become biological field stations for research or ecotourism parks which can generate employment and revenue for the community. Conservation of biodiversity is in the interest of generations unborn; not only Ghanaians or Africans but the whole of tomorrow’s mankind.